Covid-19 Vaccination and Routine Childhood Vaccinations: Comparison of Hesitancy among Parents - Mashhadi, Syed Fawad; Khan, Nazish; Ilyas, Ubaida Bin; Farooq, Omer; Waseem, Aashir; Cheema, Abdullah; Murtaza, Sahab (Pakistan Armed Forces Medical Journal, 2024)
Objectives: To assess perceptions of parents regarding vaccinating their children against COVID-19 and to assess the prevalence of COVID-19 vaccine hesitancy as compared to routine childhood vaccinations. Study Design: Analytical, cross-sectional, quantitative studyPlace and Duration of Study: Study was conducted in Rawalpindi/Islamabad Pakistan, from Nov 2021 to Apr 2022.Methodology: Parents having children of either gender, 12 to 18 years of age, residents of Rawalpindi/Islamabad Pakistan were included in the study. Study was conducted online using Google forms. Sample size of 303 was taken and participants were enrolled through non probability convenience sampling. Modified Vaccine Hesitancy Scale (VHS) was used. Parental attitudes towards routine childhood vaccinations versus COVID-19 vaccines were compared using paired sample T test.Results: Among 303 parents, 196(64.5%) were willing to vaccinate their child with COVID-19 vaccine. Reasons for COVID-19 vaccine hesitancy included insufficient vaccine safety information (16.8%), avoidance of vaccines/ medications in general (8.9%), inconvenient / painful vaccine administration (7.9%), perceiving child as not at high risk of developing complications of he gets infected by COVID-19(6.3%) and concerns of getting COVID-19 through the vaccine (4.6%). An encouraging attitude was seen among parents for routine childhood vaccination as compared to COVID-19 vaccination with higher mean VHS 2.68±0.44 vs. 2.52±0.43 respectively (p